ANALISIS PERBEDAAN RASIO KEUANGAN BANK UMUM KONVESIONAL DAN BANK UMUM SYARIAH SERTA PENGARUHNYA TERHADAP PENYALURAN KREDIT ATAU PEMBIAYAAN (Studi empiris yang tedrdaftar di BEI periode 2013-2016) - Dika Ismawati; Edy Supriyono (Magister Manajemen STIE Bank BPD Jateng, 2017)
This study aims to obtain evidence of differences in financial ratios of conventional commercial banks and sharia commercial banks, as well as the influence of financial ratios, liquidity, capital adequacy, problem loans, profitability, operating efficiency of lending. This study uses secondary data. The sample in this research is conventional commercial bank and sharia public bank listed on BEI with 4 year observation period (2013-2016). This sample was chosen by purposive sampling method. Independent sample t-test is used to test whether there is difference of average of two interconnected samples, multiple linear regression is used as data analysis technique as many as 148 general data of banking company, conventional bank and syariah commercial bank as many as 44 company data period 2013-2016 . The results of this study indicate that there are differences in average liquidity, problem loans, profitability, operating efficiency, While the average capital adequacy there is no significant difference between conventional commercial banks and sharia banks. While liquidity and profitability have a positive effect on lending, non performing loans and operating efficiency have a negative effect on lending, and capital adequacy does not affect credit disbursement.